Evolution of increased intraspecific competitive ability following introduction: The importance of relatedness among genotypes. (5th July 2018) - Zhang, Zhijie; Zhou, Fang; Pan, Xiaoyun; van Kleunen, Mark; Liu, Mu; Li, Bo
Abstract: A long‐standing explanation for invasion success is that invasive plants could evolve to be more competitive following introduction. This evolution of increased competitive ability (EICA) hypothesis, however, has seldom been tested with regard to intraspecific competition. Given that plants can display different responses to related and unrelated conspecifics, the evolution of intraspecific competitive ability might be specific to genotypes of different relatedness. Here, we grew five native (South American) and five introduced (North American) genotypes of the clonal herbaceous invasive plant Alternanthera philoxeroides alone, with above‐ground competition from kin (the same genotype) or from one of two types of strangers (another genotype from the same range or another genotype from the other range). When grown alone, introduced and native genotypes produced similar total biomass and storage‐root biomass. However, in response to intraspecific competition, introduced genotypes showed increases in total biomass and stem length, and a decrease in specific stem length, whereas native genotypes showed the opposite pattern. When grown with kin instead of strangers, introduced genotypes showed an increase in branch number, whereas native genotypes showed the opposite. Synthesis . Our study provided evidence for evolution of increased intraspecific competitive ability in an invasive plant. We also found, for the first time, that the interactions among kin were likely to shift from competition towards facilitation following introduction. Abstract : Our study provided evidence for evolution of increased intraspecific competitive responses in an invasive plant. We also found, for the first time, that the interactions among kin were likely to shift from competition towards facilitation following introduction.